1997
DOI: 10.2165/00007256-199723060-00005
|View full text |Cite
|
Sign up to set email alerts
|

Hamstring Injuries

Abstract: Pre-exercise stretching and adequate warm-up are important in the prevention of hamstring injuries. A previous mild injury or fatigue may increase the risk of injury. Hamstring muscle tear is typically partial and takes place during eccentric exercise when the muscle develops tension while lengthening, but variation in injury mechanisms is possible. Diagnosis of typical hamstring muscle injury is usually based on typical injury mechanism and clinical findings of local pain and loss of function. Diagnosis of av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
88
1
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(93 citation statements)
references
References 31 publications
1
88
1
3
Order By: Relevance
“…17 Severe (grade 3) injuries are complete or near-complete tears across a cross-section of a whole muscle 17 . For patients that suffer from moderate and severe injuries, there is often a persistent atrophy of muscle fibers, an accumulation of fibrotic scar tissue in the ECM, and a decrease in strength, functional capacity and athletic ability 15,18,19 . These patients are also much more likely to have repeated muscle injuries, with each subsequent injury resulting in greater muscle atrophy and scar tissue deposition 15,19,20 .…”
Section: Force Transmission and The Ultrastructure Of Skeletal Musclementioning
confidence: 99%
“…17 Severe (grade 3) injuries are complete or near-complete tears across a cross-section of a whole muscle 17 . For patients that suffer from moderate and severe injuries, there is often a persistent atrophy of muscle fibers, an accumulation of fibrotic scar tissue in the ECM, and a decrease in strength, functional capacity and athletic ability 15,18,19 . These patients are also much more likely to have repeated muscle injuries, with each subsequent injury resulting in greater muscle atrophy and scar tissue deposition 15,19,20 .…”
Section: Force Transmission and The Ultrastructure Of Skeletal Musclementioning
confidence: 99%
“…Immediate immobilization of the injured muscle has been shown to minimize deformation at the injury site and extent of connective tissue scar formation (27). Continued immobilization, however, has been implicated in atrophic and compromised healing, and conversely, mobilization of healing muscle is essential for myofiber growth and orientation (3, 28). The ideal timing of mobilization remains the subject of debate, and consensus is further compounded by variability of location and extent of injury.…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…(26, 55) Initial management of hamstring strains in the acute phase includes the RICE protocol of rest, ice, compression and elevation. (1, 10, 14, 34) Conservative medical management can include the use of nonsteroidal anti-inflammatory drugs (NSAIDs). (55) However, the early use of NSAIDs for acute hamstring strains is controversial, as prior studies have not demonstrated benefit.…”
Section: Treatmentmentioning
confidence: 99%
“…(4, 34, 42) Injuries can range from acute hamstring muscle strains and ruptures to chronic proximal hamstring tendinopathy. Acute hamstring strains are the most common muscle strain, have high rates of recurrence and can lead to prolonged absence from sports.…”
Section: Introductionmentioning
confidence: 99%